2018
DOI: 10.1093/nar/gky119
|View full text |Cite
|
Sign up to set email alerts
|

Combined cistrome and transcriptome analysis of SKI in AML cells identifies SKI as a co-repressor for RUNX1

Abstract: SKI is a transcriptional co-regulator and overexpressed in various human tumors, for example in acute myeloid leukemia (AML). SKI contributes to the origin and maintenance of the leukemic phenotype. Here, we use ChIP-seq and RNA-seq analysis to identify the epigenetic alterations induced by SKI overexpression in AML cells. We show that approximately two thirds of differentially expressed genes are up-regulated upon SKI deletion, of which >40% harbor SKI binding sites in their proximity, primarily in enhancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…SKI was also found to be overexpressed in AML and proposed to repress retinoic acid receptor and RUNX1mediated signaling. [53][54][55] . In addition, SKI was reported to control HSC fitness in myelodysplastic syndromes (MDS) 56 .…”
Section: Inputmentioning
confidence: 99%
“…SKI was also found to be overexpressed in AML and proposed to repress retinoic acid receptor and RUNX1mediated signaling. [53][54][55] . In addition, SKI was reported to control HSC fitness in myelodysplastic syndromes (MDS) 56 .…”
Section: Inputmentioning
confidence: 99%
“…We conclude that the increased expression of MICA and ULBP2 in PaTu8988t cells upon SKI knockdown may contribute to a better NK cell-mediated killing but SKI seems to suppress susceptibility against NK cell-mediated killing also by additional, not yet defined mechanisms. In this regard, we found in acute myeloid leukemia (AML) cells that SKI acts rather as a transcriptional repressor and inhibits target genes associated with inflammatory response, immune cell differentiation as well as TNFα signaling via NFκB [ 28 ]. Hence, SKI-expressing tumor cells may evade NK cell-killing via inhibition of pro-inflammatory factors like TNFα.…”
Section: Resultsmentioning
confidence: 99%
“…Human siGENOME SKI siRNA SMARTpool (M-003927-02-0005) and non-targeting siRNA #5 (D-001210-05) were purchased from Horizon Discovery (Waterbach, UK). ChIP-seq data were collected [ 28 ] and bioinformatical analysis are described there in the Materials & Methods section.…”
Section: Methodsmentioning
confidence: 99%
“…30 A recent study, which utilized gene expression from TCGA and transcription factor binding data from Cistrome, found that transcription factors SKI and RUNX1 occupy the same genomic sites to silence gene expression in acute myeloid leukemia. 31 This demonstrates the potential of publicly available NGS data to expand ones understanding of regulatory mechanisms in cancer.…”
Section: Ngs and Cancermentioning
confidence: 88%